Cardiac surgery in the heart transplant recipient: Outcome analysis and long‐term results. Issue 10 (30th September 2019) - Farag, Mina; Arif, Rawa; Raake, Philip; Kreusser, Michael; Karck, Matthias; Ruhparwar, Arjang; Schmack, Bastian
Abstract: Background: Survival rates following cardiac transplantation continue to improve. Due to the scarcity of available organs, extended donor criteria have become more prevalent in clinical practice. In this context, the risk of developing cardiac pathology requiring surgical correction is increasing. Methods: Between January 1991 and October 2010, a total of 479 patients received cardiac transplantations at the University Hospital Heidelberg. Of those, 18 (3.8%) patients required subsequent cardiac surgery until 2018. Short‐ and long‐term analyses were performed. Results: Indications for cardiac surgery included valvular disease (n = 16) with the majority of cases affecting the tricuspid valve (n = 10), while 6 patients received mitral valve surgery, of whom 3 patients underwent concomitant valve surgery. Other indications included CABG (n = 1) and re‐transplantation (n = 1) for allograft dysfunction. Mean follow‐up time was 6.5 years, while mean interval to surgery was 6.0 years. Early mortality was 11.1% (n = 2), while overall survival at 1, 5, and 10 years were, 88.1%, 81.4%, and 52.2%, respectively. Compared to an overall survival of that transplant cohort at 1, 5, and 10 years of 76.7%, 66.7%, and 52.4% percent, respectively ( P = .271). Conclusion: According to our data, redo cardiac surgery can be performed with acceptable mortality and morbidity. Atrioventricular valve pathology plays a chief role in these patients.